Self-assembled DNA hollow spheres from microsponges. (28th March 2019) - Choi, Daheui; Kim, Hyejin; Kim, Dajeong; Heo, Jiwoong; Lee, Hwankyu; Lee, Jong Bum; Hong, Jinkee
Abstract: We report a novel approach for generating nanosized DNA hollow spheres (HSs) using enzymatically produced DNA microsponges in a self-templating manner. In previous studies, preparation of DNA nanostructures with specified functions required multiple complicated steps. In this study, however, a simple treatment with the nucleophilic agent 4-dimethylaminopyridine (DMAP) enabled a gradual disentanglement of DNA in microsponges by electrostatic interactions between DMAP and DNA, and the DNA underwent a reassembly process to generate hollow shell structures without denaturation/annealing by thermal cycling. In addition, this synthetic process was conducted in a water-based system without organic solvents, enabling the synthesis of biologically and environmentally friendly products. Based on the benefits of hollow shell structures, which include their high surface-to-volume ratio and ability to encapsulate small molecules, we envision that this simple approach for synthesizing DNA HSs will provide a new platform for maximizing their potential use in drug delivery and bio-imaging.